Utilização do sistema de informação geográfica (SIG) na indicação de possíveis áreas aptas à disposição de resíduos de construção e de demolição - Biju, Bárbara Pavani (2015)
The construction and demolition (C&D) waste when do not have a proper final disposal; result in social, economic and environmental problems. The disposal often happens in inappropriate locations and demonstrates the necessity of adequate areas for the waste final disposal but also the selected site must be in accordance with local standards and regulations. Considering all these facts, the aim of this work is to indicate possible suitable areas for C&D waste landfill, using the Geographic Information System (GIS) tool, supported by Multi-criteria Decision Analysis (MCDA). The GIS used as a basic tool to identify possible suitable areas has several advantages: low cost; faster decision-making process and various scenarios can be analyzed simultaneously, being a valuable tool in all the construction and demolition waste management steps. Integrating GIS with MCDA has resulted in the indication of possible suitable areas for C&D waste disposal, having as a study area the Urban Central Core of Metropolitan Region of Curitiba. Keywords: Geographic Information System. Co